Determination of Formulation and Processing Factors Affecting Slowly Digestible Starch, Protein Digestibility and Antioxidant Capacity of Extruded Sorghum-Maize Composite Flour - Licata, Rebecca; Chu, Jiayue; Wang, S.; Coorey, Ranil; James, Tony; Zhao, Yun; Johnson, Stuart (Wiley-Blackwell Publishing Ltd., 2014)
High-temperature high-pressure extrusion of sorghum–maize composite flour, of potential for healthyfood manufacture, was investigated by factorial experimental design to determine the effect of level of sorghum in dry mix (15–60%); final barrel zone temperature (120–150 °C); total moisture in barrel(21.4–25.8%); total input rate (2.3–6.8 kg h -1); and screw speed (250–450 rpm) on extrudate slowlydigestible starch (SDS), phenolic content, antioxidant capacity, protein digestibility, density and expansion ratio. Extrudate SDS increased with increasing sorghum level and decreased as the barrel temperature increased. Total phenolic content and antioxidant capacity were positively associated with sorghum level. Protein digestibility was associated negatively with sorghum level and positively with barrel temperature. Extrudate density was associated positively with total moisture and negatively with barrel temperature and input rate. Sorghum in dry mix, final barrel zone temperature and total moisture in barrel were the three most significant independent variables influencing extrudate dependant variables.